PEMBAHARUAN KONSEP MAQĀSID AL-SHARĪ’AH DALAM PEMIKIRAN MUHAMAMAD ṬAHIR IBN ‘ASHUR - Chamim Tohari (Al-Maslahah : Jurnal Ilmu Syariah, 2017)
Abstract This research discuss about the thought of maqāsid al-sharī’ahby Muhammad Ṭahir Ibn ‘Ashur. To limit this discussion, i just focus to discuss two important matters, it is; First, how is concept of maqāsid al-sharī’ahin the thought of Ibn ‘Ashur? Second, how is construct of thought of the maqāsid al-sharī’ahIbn Ashur? This is a library research with content analysis as its method. The sources of this research is Ibn ‘Ashur’s thoughts in his books. The results of this research is; First, before Ibn ‘Ashur’s period, the thoughts of maqāsid al-sharī’ahhas been finding its formation in the several familier categories which mentioned by al-uṣūl al-khamsah (five of the based principles). Every principle have three level, it isdarūriyāt, al-hajjiyāt, and taḥsināt/al-tazyināt. Second, in the Ibn Ashur’s period, the thoughts of maqāsid al-sharī’ahhas renewed by Ibn ‘Ashur in the new formation as purity (al-fitrah), tolerance (al-samahah), benefit (al-maslahah), equality (al-musāwah), and freedom (al-hurriyah) as parts of the maqāsid al-sharī’ah. From the scope aspect, the validity of the Ibn ‘Ashur’s thought about maqāsid al-sharī’ahappearly have more universal character than thought of maqāsid al-sharī’ahbefore. However, the weekness of the Ibn ‘Ashur’s thought is that maqāsid al-sharī’ahthought by Ibn ‘Ashur have not clarity and explanation about the level of priority and it’s method to applicated in the Islamic Law. Abstrak Penelitian ini mengkaji tentang pemikiran maqāsid al-sharī’ahMuhammad Ṭāhir Ibn ‘Ashūr. Untuk membatasi kajian ini, penulis memfokuskan hanya pada dua masalah pokok, yakni; Pertama, bagaimana konsep maqāsid al-sharī’ahsebelum datangnya Ibn ‘Ashur? Kedua, bagaimana konstruksi pemikiran maqāsid al-sharī’ahyang digagas Ibn ‘Ashur? Penelitian ini adalah penelitian pustaka dengan konten analisis sebagai metode analisisnya. Sumber kajian ini adalah pemikiran maqāshidIbn ‘Ashur yang termuat dalam karyanya. Hasil penelitian iniadalah: Pertama, sebelum masa Ibn ‘Ashur, pemikiran maqāsid al-sharī’ahtelah menemukan bentuknya dalam beberapa kategori yang terkenal dengan istilah al-uṣūl al-khamsah, dimana masing-masing dariprinsip dasar tersebut memiliki tingkatan darūriyāt, al-hajjiyāt, dan taḥsīnāt/al-tazyīnāt. Kedua, pada masa Ibn ‘Ashur, pemikiran maqāsid al-sharī’ahmengalami pembaharuan hingga menghasilkan fitrah (al-fitrah), toleransi (al-samahah), maslahat (al-maslahah), kesetaraan (al-musawah), serta kebebasan (al-hurriyah) sebagai bagian darimaqāsid al-sharī’ah. Dari sisi cakupannya, keberlakuan maqāsid al-sharī’ahdalam pemikiran Ibn ‘Ashurtampak lebih universal dibanding dengan pemikiran maqāsid al-sharī’ahsebelumnya. Namun demikian, pemikiran Ibn ‘Ashur memiliki kelemahan darisisi ketidakjelasan tingkatan prioritasnya serta aplikasi metode penerapannya dalam hukum Islam.